Improvement in desorption kinetics of NaAlH4 catalyzed with TiO2 nanopowder - Lee, Gil-Jae; Shim, Jae-Hyeok; Cho, Young Whan; Lee, Kyung Sub (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
NaAlH4 has been homogeneously mixed with micron- and nano-sized TiO2 powders by high-energy ball milling and their sorption properties have been investigated during hydrogen absorption/desorption cycles. NaAlH4 with TiO2 nanopowder exhibits as good desorption kinetics as NaAlH4 with TiCl3, whereas poor desorption kinetics is observed with micron-sized TiO2 powder. NaAlH4 with TiO2 nanopowder also provides improved cyclic property compared to NaAlH4 with TiCl3 in terms of both desorption rate and hydrogen capacity. X-ray diffraction analysis shows that micron-sized TiO2 remains stable with NaAlH4 after milling, although thermodynamic calculation predicts that TiO2 reacts with NaAIH(4). (C) 2008 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: HYDROGEN-STORAGE MATERIALS; ALUMINUM HYDRIDES; DOPED NAALH4